Arching during the segregation of two-dimensional tapped granular systems: Mixtures versus intruders - Uñac, Rodolfo Omar (2014)
We present numerical simulations of binary mixtures of granular disks subjected to tapping. We consider the size segregation process in terms of the arches formed by small and big particles. Although arching has been proposed as one of the chief mechanisms that determines size segregation in non-convecting systems, there is no direct data on arching to support the existing proposals. The pseudo-dynamic approach chosen for this work allows for a straightforward identification of arches in the bulk of the column. We find that, indeed, arch formation and breakage are crucial to the segregation process. Our results show that the presence of large particles induce the formation of more arches than found in mono-sized samples. However, tapping leads to the progressive breakage of big arches where large particles are involved as the segregation process takes place. Interestingly, isolated intruders may or may not rise under tapping depending not only on the size ratio (as it is well known) but also on the degree of ordering of the environment.